Treto bridge refurbishment (Cantabria, 1905-2016) - M. Ruiz-Bedia; Felipe Collazos-Arias (Vitruvio: International Journal of Architectural Technology and Sustainability, 2018)
The paper delves into the process of refurbishment of an old metal bridge (year 1905) located in a marsh (mouth of the Ason river, Cantabria) of high environmental value. The repair was necessary to guarantee the structural safety  of  the  bridge,  which  serves  a  national  road  (N-634).  At  the  same  time,  it  was  necessary  to  preserve  its cultural values and, during the work, to fulfill the environmental requirements. The  text  emphasizes  the  importance  of  having  a  good  record  of  information  on  the  bridge  in  order  to  plan  a good intervention. The results confirm that the previous studies have been useful to project and execute a deep repair, respecting the cultural landscape of the estuary.